2009
DOI: 10.1158/0008-5472.can-08-4021
|View full text |Cite
|
Sign up to set email alerts
|

The Activated Notch1 Signal Pathway Is Associated with Gastric Cancer Progression through Cyclooxygenase-2

Abstract: Gastric carcinoma is one of the most common cancers and lethal malignancies worldwide. Thus far, the regulatory mechanisms of its aggressiveness are still poorly understood.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
150
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(160 citation statements)
references
References 51 publications
(70 reference statements)
4
150
2
1
Order By: Relevance
“…Illustrating the diverging impact of Notch according to histological subgroups, we report, for the first time, Notch-1 as an independent negative prognostic factor in NSCLC patients with AC. Our findings corroborate previous results in other malignancies, such as breast 15 and gastric cancer, 16 but are in contrast to results from a colorectal study, 17 where no association was found, and a bladder cancer study 18 reporting high Notch-1 expression to indicate a good prognosis. In an IHC study of 153 NSCLC patients, Lee et al reported Notch-1 to be negatively correlated to lymph node metastasis, but did not show any prognostic value.…”
Section: Discussionsupporting
confidence: 89%
“…Illustrating the diverging impact of Notch according to histological subgroups, we report, for the first time, Notch-1 as an independent negative prognostic factor in NSCLC patients with AC. Our findings corroborate previous results in other malignancies, such as breast 15 and gastric cancer, 16 but are in contrast to results from a colorectal study, 17 where no association was found, and a bladder cancer study 18 reporting high Notch-1 expression to indicate a good prognosis. In an IHC study of 153 NSCLC patients, Lee et al reported Notch-1 to be negatively correlated to lymph node metastasis, but did not show any prognostic value.…”
Section: Discussionsupporting
confidence: 89%
“…16 In addition, activation of notch1 signal pathway was confirmed to promote invasion and colony formation ability of gastric cancer through COX-2. 17 Conversely, transfection of constitutive notch1 plasmid led to growth inhibition in thyroid cancer cells, DRO and FTC236. 18 In GBM, notch1 and its ligands are reported to be overexpressed, and knockdown of notch1 induces apoptosis and inhibits proliferation.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…The Notch 1 signaling pathway, in particular, draws great attention in the research of the Notch signaling pathway in GC. At present, Notch 1 seems to function as an oncoprotein in GC, as evidenced by a recent report that Notch 1 contributed to GC progression by inducing COX2 expression (71). Furthermore, Yao et al (72) reported that activation of the Notch 1 receptor can reduce TNFα-induced apoptosis in BGC-823 cells.…”
Section: Breast Cancermentioning
confidence: 97%